Comparison of Proportion and Resistance Ratio Methods for Drug Susceptibility Testing of Mycobacterium tuberculosis Isolated from Patients Attending National Tuberculosis Centre, Nepal - Acharya, S; Ghimire, P; Khadka, DK; Nepali, S (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Background: Tuberculosis (TB) is among the most serious infectious cause of global morbidity and mortality. Emergence of Multi-drug resistant tuberculosis (MDR-TB) is posing an increased threat to TB control programs. Drug susceptibility testing (DST) of Mycobacterium tuberculosis (M. tuberculosis) isolates is important for tackling such problems. Setting: National Tuberculosis Centre (NTC), Thimi, Bhaktapur, Nepal. Objectives: Comparative evaluation of two in vitro DST methods in determining susceptibility of M. tuberculosis isolates from patients attending NTC, to front-line anti-TB drugs: (Isoniazid-INH, Rifampicin-RFP, Streptomycin-SM, and Ethambutol-EMB). Methodology: This study was conducted from Sep 2006-Jun 2007. A total of 862 sputum samples (diagnosis or follow up cases) collected from patients (type of patients or their categories was not differentiated in this study) attending NTC bacteriology lab for sputum direct smear microscopy were analyzed using fluorescence microscopy. All smear positive samples, smear negative samples requested for culture were cultured. All culture positive samples confirmed as M. tuberculosis by biochemical tests were processed for DST by both proportion (PR) and resistance ratio (RR) methods. Results: Out of 862 sputum samples analyzed, 226 (26.2%) samples were positive for Acid Fast Bacilli (AFB) by fluorescence microscopy. Among 323 samples 226 smear positive samples and 97 smear negative samples requested for culture), 221 (68.4%) were culture positive, 92 (28.5%) were culture negative and 10 (3.1%) were contaminated. Out of 221 isolates of M. tuberculosis, 57.5% were resistant to one or more drugs by the PR method and 56.6% by the RR method. Similarly, MDR isolates were 29.9% and 29% by PR and RR methods respectively. On correlation analysis using Mc Nemar Chi-square test, no significant difference between the two tests were observed (p>0.05). The results showed high agreement between both methods and agreement rates to INH, RFP, SM and EMB were 93.2%, 93.7%, 93.2% and 94.1% respectively. Similarly, the agreement rates between both methods using kappa analysis showed kappa (k) value of 0.86, 0.85, 0.86 and 0.84 for INH, RFP, SM and EMB respectively, which is believed to be good agreement between both methods (k=0.80 to 1.00: Very good agreement). Conclusion: In conclusion, this study showed that both the Proportion and Resistance ratio methods are equally good for determining drug susceptibility of M. tuberculosis. Keywords: Mycobacterium tuberculosis; Drug Susceptibility Testing; Proportion Method; Resistance Ratio Method. DOI: 10.3126/saarctb.v5i1.3078 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(1) 13-20